Sedentary time and its association with risk of cardiovascular diseases in adults: an updated systematic review and meta-analysis of observational studies - Wu Jingjie; Lili Yang; Ye Jing; Lulu Ran; Xu Yiqing; Na Zhou (BMC, 2022)
Abstract Background Epidemiological studies assessing the association between sedentary time and cardiovascular diseases (CVD) risks have been published at a rapid pace in recent years, which makes the periodic review of knowledge essential. Furthermore, much of the early and ongoing work used screen time as a marker of total sedentary time, which may weaken the association between sedentary time and CVD risks. Objective To update evidence on CVD risks associated with different types of sedentary time, especially total sedentary time and screen time, and to explore as a marker of total sedentary time, whether screen time had similar CVD risks with total sedentary time. Methods PRISMA guideline was followed for the performing and reporting of this systematic review and meta-analysis. Three independent researchers searched eight electronic databases and two clinical trial registries for all studies published between January 2015 and December 2021 that assessed the association between sedentary time and CVD risks in adults. A standardized form was used for data extraction and collection. Wilmot and colleagues' modified tool was used for quality assessment. The categorical association was assessed by comparing the pooled effect sizes for CVD risks associated with the highest and the lowest sedentary time categories across included studies. Stata 16.0 and Review Manager 5.3 were used for all statistical analyses, P ≤ 0.05 was considered as statistically significant. Results Seventeen prospective cohort studies and two cross-sectional studies with 145,1730 participants and over 48,668 CVD cases and deaths were included. Two included studies measured sedentary time with the accelerometer, 16 studies with self-reported questions, and one study with both the accelerometer and self-reported questions. CVD outcomes were self-reported in two included studies and objectively adjudicated through medical records or death certifications in 17 studies. Compared with the lowest total sedentary time category (median duration, 2.75 h/d), participants in the highest category (median duration, 10.5 h/d) had an increased risk of CVD morbidity (pooled RR, 1.24; 95% CI, 1.21-1.27). Compared with the lowest total sedentary time category (median duration, 2.98 h/d), participants in the highest category (median duration, 10.2 h/d) had an increased risk of CVD mortality (pooled HR, 1.29; 95% CI, 1.13-1.47). The association between screen time and CVD risks was similar to total sedentary time with the cut-off point of 5-6 h/d. The associations between occupational sitting time, leisure sedentary time, and CVD risks stayed inconclusive. Conclusion Total sedentary time and screen time are both associated with cardiovascular health. As a marker of total sedentary time, screen time over 5-6 h/d had similar CVD risks with total sedentary time over 10-11 h/d.